Myocardial infarction in relation to mercury and fatty acids from fish: a risk-benefit analysis based on pooled Finnish and Swedish data in men - Wennberg, Maria; Strömberg, Ulf; Bergdahl, Ingvar A; Jansson, Jan-Håkan; Kauhanen, Jussi; Norberg, Margareta; Salonen, Jukka T; Skerfving, Staffan; Tuomainen, Tomi-Pekka; Vessby, Bengt; Virtanen, Jyrki K (The American journal of clinical nutrition, 2012)
Background: Exposure to methylmercury from fish has been associated with increased risk of myocardial infarction (MI) in some studies. At the same time, marine n−3 (omega-3) PUFAs are an inherent constituent of fish and are regarded as beneficial. To our knowledge, no risk-benefit model on the basis of data on methylmercury, PUFA, and MI risk has yet been presented.Objective: The objective of this study was to describe how exposure to both marine n−3 PUFAs and methylmercury relates to MI risk by using data from Finland and Sweden.Design: We used matched case-control sets from Sweden and Finland that were nested in population-based, prospective cohort studies. We included 361 men with MI from Sweden and 211 men with MI from Finland. MI risk was estimated in a logistic regression model with the amount of mercury in hair (hair-Hg) and concentrations of n−3 PUFAs (EPA and DHA) in serum (S-PUFA) as independent variables.Results: The median hair-Hg was 0.57 μg/g in Swedish and 1.32 μg/g in Finnish control subjects, whereas the percentage of S-PUFA was 4.21% and 3.83%, respectively. In combined analysis, hair-Hg was associated with higher (P = 0.005) and S-PUFA with lower (P = 0.011) MI risk. Our model indicated that even a small change in fish consumption (ie, by increasing S-PUFA by 1%) would prevent 7% of MIs, despite a small increase in mercury exposure. However, at a high hair-Hg, the modeled beneficial effect of PUFA on MI risk was counteracted by methylmercury.Conclusions: Exposure to methylmercury was associated with increased risk of MI, and higher S-PUFA concentrations were associated with decreased risk of MI. Thus, MI risk may be reduced by the consumption of fish high in PUFAs and low in methylmercury.